Lower Insulin-Dose Adjusted A1c (IDAA1c) Is Associated With Less Complications in Individuals With Type 1 Diabetes Treated With Hematopoetic Stem-Cell Transplantation and Conventional Therapy - Penaforte-Saboia, Jaquellyne Gurgel; Couri, Carlos Eduardo Barra; Fernandes, Virginia Oliveira; Montenegro, Ana Paula Dias Rangel; Batista, Lívia Aline De Araújo; Zajdenverg, Lenita; Negrato, Carlos Antonio; Malmegrim, Kelen Cristina Ribeiro; Moraes, Daniela Aparecida; Dias, Juliana Bernardes Elias; Oliveira, Maria Carolina; Hussain, Akhtar; et al. (Frontiers in Endocrinology, 2019)
OBJECTIVE: To evaluate the association between insulin-dose adjusted A1C (IDAA1c) and microvascular complications (MC) and hypoglycemia in a representative Brazilian population of Type 1 diabetes mellitus (T1DM) patients. RESEARCH DESIGN AND METHODS: This was a cross-sectional study based on a previous study, “Microvascular Complications in Type 1 Diabetes: a comparative analysis of patients treated with autologous nonmyeloablative hematopoietic stem-cell transplantation (AHST) and conventional medical therapy (CT)”. The 168 patients in that study (144 from CT plus 24 from AHST) were re-subdivided into two groups, according to their IDAA1c values (30 patients had IDAA1c ≤9; 138 had IDAA1c >9). Then, the prevalence of MC (diabetic renal disease, neuropathy, and retinopathy), hypoglycemia (blood glucose <60 mg/dL), and severe hypoglycemic (episode of hypoglycemia that required the assistance of another person to treat) events were compared between the groups. The groups were well-matched on these factors: duration of disease, sex, and age at the time of diagnosis of T1DM. RESULTS: After an average of 8 years after diagnosis, only 6.6% (2/30) of the patients from IDAA1c ≤ 9 group developed any MC, whereas 21.0% (29/138) from the IDAA1c >9 group had at least one complication (p =0.044). Regarding hypoglycemic events, the proportion of individuals who reported at least 1 episode of hypoglycemia in the last month was 43.3% and 64.7% from the IDAA1c ≤9 and IDAA1c >9 groups, respectively (p=0.030). Regarding severe hypoglycemia, the proportion of patients presenting at least 1 episode in the last month and the rate of episode/patient/month were similar between groups (6.7% vs 13.2%; p= 0.535; and 0.1/patient/month vs 0,25/patient/month; p= 0.321). CONCLUSION: In a representative Brazilian population of T1DM patients, those with IDAA1c ≤9 presented a lower frequency of MC, as well as fewer episodes of hypoglycemia, in the month prior to the analysis.